Revisiting Governance Determinants of Public Service Performance: Empirical Evidence on Transparency and Accountability from Pakpak Bharat (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study examines the influence of transparency and accountability on the performance of public service delivery in Pakpak Bharat Regency. Using a quantitative research design, data were collected through questionnaires administered to residents who accessed public services provided by local government institutions. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM‑PLS) to evaluate the relationships among the studied variables. The findings reveal that both transparency and accountability have a significant positive effect on public service performance, with transparency demonstrating a stronger influence compared to accountability. These results indicate that improving openness in governmental decision‑making processes and strengthening accountability mechanisms in the execution of public duties are essential strategies for enhancing service quality. The study provides practical implications for local governments, emphasizing the need to formulate policies that promote transparent governance and reinforce accountability structures to increase the effectiveness and efficiency of public service delivery. Overall, this research contributes to the growing body of literature on public sector governance by highlighting the critical role of transparency and accountability in improving public service outcomes at the regional level.